Effect of 3D Modeling of S-fusion software on Positive surgical Margins in Patients who Underwent Radical Retropubic Prostatectomy: A Randomized Prospective Study - Oguz, Ural; Bekçi, Tümay; Öğreden, Ercan; Aslan, Serdar; Tok, Birgül; Tok, Doğan Sabri; Akyol, Safa; Altun, Ertürk; Demirelli, Erhan (Urology Journal, 2025)
Purpose: To investigate the effect of using three-dimensional (3D) modeling before the surgery on positive surgical margins (PSM) in patients who underwent radical retropubic prostatectomy (RRP). Materials and Methods: A prospective data analysis of 81 patients who underwent RRP between April 2021 and December 2023 was performed. Patients were randomized into 2 groups. In “3D group” (n:41), patients were evaluated by the surgeon and radiologist by using a 3D modeling of the mpMRI images which were done by two experienced radiologists just before the surgery. In “non-3D group” (n:40), the surgeon evaluated the mpMRI scans and reports by himself without a 3D modeling of the mpMRI before the operation. Finally, positive surgical margins of two groups were compared. Results: The mean age of the patients was 66.7 ± 5.2 and 65.3±4.9 years in 3D group and non-3D group, respectively. (p = .65) Preoperative PSA value, prostate volume, preoperative PIRADS 4 and PIRADS 5 scores, postoperative ISUP grades and T stages were statistically similar in both groups. (p > .05) The PSM rate was 24 (29.6%) in the overall patient population. PSM was detected in 6 (14.6%) and 18 (45%) of the patients in 3D group and non-3D group, respectively. (p = .005) Conclusion: Using a 3D modeling of the mpMRI images before the surgery decreased the PSM rates after radical retropubic prostatectomy. The present study also reveals the importance of collaboration between radiologists and urologists in the accurate preoperative evaluation of prostate cancer.